Learning Strategies Used by the Students in Performance Assessment in EFL Classroom - Ida Dwi Safitri; Sumardi Sumardi; Slamet Supriyadi (Bina Nusantara University, 2018)
This research aimed to discuss performance assessment in Indonesia as well as learning strategies used by the students in its implementation. A qualitative case study was applied in this research. The researchers spread questionnaire and conducted an in-depth interview to derive the data. From the discussion, some conclusions are derived. First, performance assessment has advantages in EFL such as promoting high order thinking skill, making students familiar with various contexts of language use, presenting tasks which allow students to apply their knowledge and skills from several learning targets, using clearly defined criteria to evaluate how well the student has achieved this application, and increasing students’ motivation. However, there are disadvantages from this kind of assessment such as time-consuming, the assessment tends to be subjective, requiring intensive training for raters, and it may intimidate students. Furthermore, the students apply almost all of the learning strategies as follows meta-cognitive, cognitive, social, and affective strategies. The contribution offered by this research is to give evidence prevailing to Indonesian EFL learning. The teacher can support or provide students’ need by knowing their students’ strategies in learning. However, the students can adjust their learning strategies when performance assessment is implemented.